2018
DOI: 10.3390/ijms19010131
|View full text |Cite
|
Sign up to set email alerts
|

Development of Burdock Root Inulin/Chitosan Blend Films Containing Oregano and Thyme Essential Oils

Abstract: In this study, inulin (INU) extracted from burdock root was utilized as a new film base material and combined with chitosan (CHI) to prepare composite films. Oregano and thyme essential oils (OT) were incorporated into the INU-CHI film to confer the films with bioactivities. The physical and optical properties as well as antioxidant and antimicrobial activities of the films were evaluated. INU film alone showed poor physical properties. In contrast, the compatibility of INU and CHI demonstrated by the changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The authors later investigated the migration of the antioxidants from the prepared films and observed that those incorporating ginger, sage, or rosemary EO showed the highest diffusion and antioxidant activity [49]. Cao et al synthetized a biofilm from chitosan and inulin, which is a polysaccharide extracted from burdock root, also incorporating oregano and thyme essential oils [50]. Films prepared with both polymers showed better physicochemical properties, such as increased textile strength and elongation to break, compared to those without chitosan.…”
Section: Polymeric Formulationsmentioning
confidence: 99%
“…The authors later investigated the migration of the antioxidants from the prepared films and observed that those incorporating ginger, sage, or rosemary EO showed the highest diffusion and antioxidant activity [49]. Cao et al synthetized a biofilm from chitosan and inulin, which is a polysaccharide extracted from burdock root, also incorporating oregano and thyme essential oils [50]. Films prepared with both polymers showed better physicochemical properties, such as increased textile strength and elongation to break, compared to those without chitosan.…”
Section: Polymeric Formulationsmentioning
confidence: 99%
“…The application of such packages is investigated for numerous types of raw or processed foods such as pork, ham, chicken wingettes, fish fillets, seafood, vegetables, fruits, juices, etc. [39,40,[45][46][47][48][49][50][51][52]. The incorporation of 2% OrO in a chitosan-based biocomposite film achieved a growth inhibition rate of 99% against E. coli and L. monocytogenes [41].…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of the food industry, OrO is often not added to the product itself, but is incorporated into biocomposite packaging films or other types of edible coatings. Edible coatings based on polysaccharides are environmentally friendly alternatives and can reduce the use of chemical preservatives [39][40][41][42][43][44]. The application of such packages is investigated for numerous types of raw or processed foods such as pork, ham, chicken wingettes, fish fillets, seafood, vegetables, fruits, juices, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Application of these polysaccharides to modify the properties of starch gels has already been presented in the literature [ 12 ]. In the available literature, there are also researches in which inulin, in concentrations in the range of 0.1–4 g/100 g, is a functional additive to chitosan or alginate gels, and the purpose of its use is to improve the properties of these gels or bio-films or microcapsule walls, which are formed from aqueous solutions of these polysaccharides [ 13 , 14 , 15 , 16 , 17 ]. However, the question of what effect the addition of SA and CH has on the characteristics of inulin gels is not known.…”
Section: Introductionmentioning
confidence: 99%